Space as a source of alienation in the context of migration debates - Ulubay, Serhat; Onal, Feride (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2022)
Migration is one of the main agenda items of the time we live in. Migration mobility, which is defined as an act of displacement in its basic meaning corresponds to a process affecting many dynamics. It does not seem possible to make an overarching immigration definition due to the reasons for its emergence, the effect it creates on the social structure and the difference in its results. The phenomenon of immigration existing in the literature with definitions closer to its essential sense such as 'spatial mobility', 'act of displacement', 'transition from one place to another with the intention of settlement' does not contain the content of an absolute border crossing action. Crossing a border does not end the act of migration, but immigrants encounter ethnic, religious, social, class and many other thresholds and borders. For this reason, migration is not just an act of displacement. Immigrants migrate to places, cultures, social structures, life and many other aspects of new geographies. Social elements and spaces established with daily lives are one of the thresholds faced by the immigrant. Immigrants are stuck between the places in their geographies and the places and lifestyles in their new places where they came through immigration. This contrast manifests itself as soon as they step into a new geography and this situation transforms into an element of oppression for immigrants. The migration does not only correspond to the loss of physical spaces, but also to the dissipation of all social and daily life. For that reason, Arent, Heidegger and Blanchot define migrations of the current time period is independent of a physical displacement, alienation from the social and daily life acts to which one belongs and estrangement of the individual from his own essence. Alienation of one's own self, identity and sociality, drags them into an everlasting migration. For this reason, Blanchot emphasises that immigration starts as soon as the immigrant gets used to the places where he/she migrates, not when he/she fails to get used to the places. It is worth remembering that the space cited here has abstract content as well as concrete construction activity. Space according to Lefebvre exists as a product of the cultural, social and historical acts of societies. For this reason, it is specific to a community. It incorporates not only a concreteness, but also the mentality containing the traces of communities. Space represents a critical threshold in debates about immigration. For immigrants, space is both the grounds fin- establishing a sense of belonging and preserving their own identity, as well as the source of alienation and mental migration. This contrast is discussed in the study through Derrida's hospitality statement and the concepts of spatial memory and belonging. Immigrant according to Derrida, encounters a sovereign power defining itself as the owner of the place, in other words, the host, in the geography where he migrated. The host offers a place to the immigrant, whom he/she sees as a guest, and hosts him/her in his home. In fact, the landlord defines where, how and in what way he or she will live, together with the space and draws limits to him/ her. That he/she presents his/her way of life to the immigrant as if it were a rule that he/she must abide by. This style of presentation is a kind of imposition, because it doesn't contain any preference option in it: I host you in my home. Welcome to my home, save to adhere my language, tradition, lifestyle, laws and rules. This language of life that the immigrant does not recognise and is not familiar with, is an act of mental 'violence perpetrated against him/her. This act of violence takes place through space. Although the immigrant loses his/her place by experiencing a physical migration, he/she brings all the acts of his social and daily life with him/her through his memory. These acts kept in the memory, stands out as the founding elements of the space in the new lands. Immigrants attempt to create their own spaces and lives through their memories instead of venues and lifestyles offered to them. For this reason, space is also the opposite of mental migration and alienation as the preservation of ego and identity. The space, in the migration actions that took place in the current time period, on one hand, is the main actor of eternal immigration and on the other hand protecting identity. The immigrant is stuck between the space offered to him/her and his/her actions and spatial memory in the new lands he/she has come from. The study aims to examine the situation of the immigrant, to question the source of alienation and (main) migration over this sense incorporated by the space.
Keywords: Belonging; landlord; immigration; guest; spatial memory; foreigner; Architecture